28 years of traceability management: trends, bottlenecks and opportunities. (2019) - Kamann, Dirk-Jan F.; Alfaro, José A.; Sebrek, Szabolcs Szilárd
This paper shows the evolution of traceability management from 1990-2017 using 124 articles. It lists 73 journals by name, classified in 12 fields of science. We find a dominance of food journals, with journals in supply chain management and IT in a stable second and third position. Articles are coded for nine possible topics and divided into two categories: theoretical and empirical. An increasing Berry index for the nine topics shows an increased dispersion across the various topics. Out of the 43 case studies, 36 relate to the food industry, although more recent publications also deal with other sectors. Various relevant theories are discussed and observed bottlenecks are discussed as well as future potential, like using systems thinking with big data analysis as an enabler.